2021
DOI: 10.1021/acsenergylett.1c01311
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Long-Term Stability of Pure Formamidinium Perovskite Solar Cells by Ambient Air Additive Assisted Fabrication

Abstract: Due to the high industrial interest for perovskite-based photovoltaic devices, there is an urgent need to fabricate them under ambient atmosphere, not limited to low relative humidity (RH) conditions. The formamidinium lead iodide (FAPI) perovskite α-black phase is not stable at room temperature and is challenging to stabilize in an ambient environment. In this work, we show that pure FAPI perovskite solar cells (PSCs) have a dramatic increase of device long-term stability when prepared under ambient air compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 70 publications
2
77
0
Order By: Relevance
“… 119 Salim et al also further showed that the long-term stability of NMP additive-pure FAPbI 3 PSCs shows a dramatic increase when prepared under ambient air compared to PSCs made under nitrogen. 120 Ma et al incorporated methylamine thiocyanate as a stabilizer, and high-quality and stable α-phase FA-based perovskites in ambient 50 ± 5% RH even at room temperature. 121 Only Huang et al 119 really prepared the FAPbI 3 PSCs at high humidity in the atmospheric air and obtained excellent stability.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“… 119 Salim et al also further showed that the long-term stability of NMP additive-pure FAPbI 3 PSCs shows a dramatic increase when prepared under ambient air compared to PSCs made under nitrogen. 120 Ma et al incorporated methylamine thiocyanate as a stabilizer, and high-quality and stable α-phase FA-based perovskites in ambient 50 ± 5% RH even at room temperature. 121 Only Huang et al 119 really prepared the FAPbI 3 PSCs at high humidity in the atmospheric air and obtained excellent stability.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…1f displays the O 1s peaks for the perovskite lms prepared with different atmospheres. The O 1s peaks are located at 529.8 eV and 531.1 eV in the air-CsPbI 2 Br lm, which are attributed to oxygen atoms in metal-oxide bonds 18 and superoxide (O 2…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 2f,g, the peaks at 14.11°, 24.45°, and 28.28° were indexed to the (100), (111), and (200) lattice planes of the typical perovskite, respectively. [ 36 ] Compared to the control film, there are no additional peaks, and no peak shifts for the films treated by ZnPP treatment, manifesting that the ZnPP molecular was only attached to the interface and surface of perovskite film and did not change the crystal structure of the perovskite. [ 37 ] However, the target samples exhibited stronger diffraction intensities and narrower full widths at half maximum (FWHM) at 2 θ = 14.11°, especially for the 0.05 mg mL −1 ZnPP‐treated film, in which the FWHM decreased from 0.090° (control film) to 0.073° (Figure 2g).…”
Section: Resultsmentioning
confidence: 99%